Peran Brand Image, Word of Mouth dan Trust dalam Mempengaruhi Kepuasan Pelanggan terhadap Klinik Kecantikan Ms Glow di Sidoarjo - Octavia, Rena Salsabil; Komala Sari, Dewi; Oetarjo, Mas (Journal of Management and Bussines (JOMB), 2024)
This study aims to determine the role of Brand Image, Word of Mouth (WoM), and Trust in influencing Customer Satisfaction at the MS Glow beauty clinic. This study uses a quantitative approach with the population being the people of Sidoarjo Regency who have used products and undergone treatment at the MS Glow beauty clinic and are aged ≥17 - 55 years. The sampling technique for this study was carried out using the non-probability sampling method with a purposive sampling technique with a total of 100 respondents. The collection technique by distributing questionnaires and answers will be measured using a Likert scale. The data analysis technique in this study uses the PLS-SEM method with the help of SmartPLS 3.0 software. The results of this study prove that Brand Image influences customer satisfaction at the MS Glow beauty clinic in Sidoarjo, Word of Mouth (WoM) influences customer satisfaction at the MS Glow beauty clinic in Sidoarjo and Trust influences customer satisfaction at the MS Glow beauty clinic in Sidoarjo. Keywords: Brand Image, Word of Mouth (WoM), Trust, Customer Satisfaction